Cardiovascular Risk Factors in Premature Ovarian Insufficiency using Hormonal Therapy - Rezende, Gabriela Pravatta; Dassie, Thamyse; Gomes, Daniela Angerame Yela; Benetti-Pinto, Cristina Laguna (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective Premature ovarian insufficiency (POI) is characterized by early hypoestrogenism. An increased risk of cardiovascular (CV) disease is a long-term consequence of POI. A challenge of hormone therapy (HT) is to reduce the CV risk.Methods Cross-sectional study with lipid profile analysis (total cholesterol, LDL-C, HDL-C, VLDL-C and triglycerides), blood glucose levels and arterial blood pressure of women with POI using HT, compared with age and BMI-matched women with normal ovarian function (controls).Results The mean age and BMI of 102 POI patients using HT and 102 controls were 37.2 ± 6.0 and 37.3 ± 5.9 years, respectively; 27.0 ± 5.2 and 27.1 ± 5.4 kg/m2. There wasn't difference between groups in arterial systolic and diastolic blood pressure, blood glucose levels, total cholesterol, LDL-C, VLDL-C and triglycerides. HDL-C levels were significantly higher in the POI group (56.3 ± 14.6 and 52 ± 13.9mg/dL; p = 0.03). Arterial hypertension was the most prevalent chronic disease (12% in the POI group, 19% in the control group, p = ns), followed by dyslipidemia (6 and 5%, in POI and control women).Conclusion Women with POI using HT have blood pressure levels, lipid and glycemic profile and prevalence of hypertension and dyslipidemia similar to women of the same age and BMI with preserved gonadal function, in addition to better HDL levels.
Keywords: premature ovarian insufficiency; cardiovascular disease; secondary amenorrhea; hormonal therapy; cardiometabolic risk factors